2013
DOI: 10.1186/1471-2458-13-1194
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy and consistency of weights provided by home bathroom scales

Abstract: BackgroundSelf-reported body weight is often used for calculation of Body Mass Index because it is easy to collect. Little is known about sources of error introduced by using bathroom scales to measure weight at home. The objective of this study was to evaluate the accuracy and consistency of digital versus dial-type bathroom scales commonly used for self-reported weight.MethodsParticipants brought functioning bathroom scales (n = 18 dial-type, n = 43 digital-type) to a central location. Trained researchers as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 23 publications
0
50
0
Order By: Relevance
“…For example, as you add weight, your clothes become tighter and you can quantify any weight change by stepping on the bathroom scales. However, it is easy to rationalize tighter clothes (they have shrunk in the wash) and the scales themselves may not be very accurate and provide unreliable feedback on body weight (e.g., Yorkin, Spaccarotella, Martin‐Biggers, Virginia Quick, & Byrd‐Bredbenner, ). Additionally, many people, particularly men (see e.g., Striegel‐Moore et al ., ), may not check their weight unless they have a reason to do so.…”
Section: Discussionmentioning
confidence: 99%
“…For example, as you add weight, your clothes become tighter and you can quantify any weight change by stepping on the bathroom scales. However, it is easy to rationalize tighter clothes (they have shrunk in the wash) and the scales themselves may not be very accurate and provide unreliable feedback on body weight (e.g., Yorkin, Spaccarotella, Martin‐Biggers, Virginia Quick, & Byrd‐Bredbenner, ). Additionally, many people, particularly men (see e.g., Striegel‐Moore et al ., ), may not check their weight unless they have a reason to do so.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the bathroom weighing scale was reset to zero before each use. Yorkin et al (2013) have reported that a digital home bathroom weighing scale offers adequately precise and reliable weights for public health research. Prompt reset to zero scale before each use could promote precision of weight measurements (Yorkin et al 2013).…”
Section: Validity and Reliability Of The Instrumentmentioning
confidence: 99%
“…It has a validity and intra-rater reliability index of 0.9 and 0.95 respectively. 24 Height meter: This was used to measure the participants' height. It is normally made from a ruler and a horizontal headpiece that is sliding and can be adjusted to rest on the top of the head.…”
Section: Adapted Cable Tensiometer (Camry Emperors Model: Iso9001)mentioning
confidence: 99%